Experimental assessment and modeling of solar air heater with V shape roughness on absorber plate - Kumar, Rahul (2023)
A roughness of the absorber plate can improve the efficiency of a solar air heater. To boost the efficiency of triangle solar air heaters, this research presents the results of a comparison study between with and without rib roughness on absorber plates. Both use black paint with graphene nanoparticles infused into it, coating an absorber plate. Both numerical and experimental methods have been used to examine the impact of surface roughness on friction factors and heat transport properties. ANSYS 14.5 software module and RNG turbulence, k-€ model is used to conduct a three-dimensional simulation and solve the governing equations in the turbulent situation. Based on experimental data, it has been established that smooth plates are more efficient in converting heat into useful work than rough ones, on average, by a factor of 4.82 and 4.46, respectively. The length of the duct in the solar air heater mitigates the temperature gradient seen in the simulation result. The roughness of V-shaped ribs has a far larger effect on the heat transfer and friction factor properties than do variations in relative roughness pitch (P/e) and Reynolds number (Re). Experimental observations supported by modeling and simulation confirms that triangular duct absorber surface roughness provides improved outcome.